Information and analytical support of production stocks management at the enterprise for crisis prevention (Economics and region, 2023)
The use of information support and automated methods of analysis of production stocks are important factors affecting the efficiency of the enterprise. This is especially relevant for enterprises operating in conditions of an unstable economy and experiencing the threat of crisis phenomena in economic activity. Automation of the process of analysis of production stocks allows to increase the efficiency of stock management and to ensure more accurate and up-to-date management decisions. The article considers the role and importance of information support and methods of analysis of production stocks at agricultural enterprises. Among others, it is proposed to use the following methods: economic-statistical, ABC-, XYZ-, functional-cost analysis, etc. The authors emphasize that the use of software, complexes and IT databases can improve production efficiency by providing accurate planning, analysis and control of stocks, raw materials and materials, as well as improving communication with suppliers. The article highlights the benefits of automated inventory analysis, such as faster data collection and analysis, timely identification of material needs, reduced resource wastage, and improved production forecasting accuracy. Thus, the authors of the article recommend using modern information technologies and inventory management systems to improve the efficiency and profitability of agricultural enterprises and to prevent the risk of a crisis on them.
Keywords: production stocks; analysis; information and analytical support; automation; management; crisis prevention